1437 Early detection of asbestos-related lung cancer by low-dose multislice-ct (low-dose msct). (24th April 2018) - Harth, V
Abstract : Introduction: Lung cancer is the most common cause of death from cancer worldwide, estimated to be responsible for nearly one in five (18%), or 1.38 million, cancer deaths in 2008. Of all risk factors, smoking has been identified as the major risk factor. Other causes of lung cancer include occupational (e.g. asbestos) and environmental exposures (e.g. radon decay products). Despite the reduction or ban of asbestos use in many countries, the global incidence of asbestos-related lung cancer is still increasing. Nevertheless, asbestos is still produced and exported in some countries in the world. The National Lung Screening Trial (NLST) enrolled persons at high risk for lung cancer to undergo annual screenings with either low-dose CT or single-view posteroanterior chest radiography. In the low CT-group, mortality from lung cancer was reduced by 20.0%. Currently, secondary prevention strategies are extensively discussed to reduce mortality from lung cancer. Methods: In Germany, more than 80% of lung cancers are diagnosed at an advanced disease stage (clinical stages IIIa, IIIb, and IV) where the survival rate is poor. Since lung cancer is only curable at an early stage of the disease, in Germany, formerly asbestos-exposed insured individuals have the statutory right to receive 'follow-up occupational medical examinations' which target the early detection of asbestos-related diseases. Recently, the German Social Accident Insurance (DGUV) founded a working group to establish an annual low-dose MSCT scanning program. Results: The eligibility criteria for participants are: at least 10 years of exposure to asbestos (starting before 1985) or a recognised case of asbestos-induced occupational disease (No. 4103 BKV), between 55 and 74 years of age and a history of cigarette smoking of at least 30 pack years. The participants are contacted by GVS (a joint organisation involving all German social accident insurance institutions) or the specific statutory accident insurance and examinations are offered which are carried out locally by selected physicians. A quit-smoking counselling is provided, and participants are asked to donate blood for biomarker research. For MSCT scanning, at least 16 row scanners are mandatory. The evaluation algorithm follows the recommendation of the National Comprehensive Cancer Network (NCCN Guideline) which specifies interventions according to nodule size. Suspicious findings lead to individual assessment by a pulmonologist and could imply CT control after several weeks, PET imaging, or immediate biopsy. Clinical workup and treatment for malignancies follow the respective guidelines. Conclusion: In Germany, formerly asbestos-exposed insured individuals have the statutory right to receive 'follow-up occupational medical examinations' (secondary prevention). Due to the results of the NLST-Study, the DGUV decided to offer an annual low-dose CT to a highly selected population of former asbestos-exposed workers and workers with asbestos-induced recognised occupational disease. Hereby, we present results of this early detection program.